RESEARCH ON PARAMETRIC MODELING METHOD FOR RESIDUAL STRENGTH OF SUBSEA OIL AND GAS PIPELINE - ZHOU HongMing; ZHOU WenQing; MAO ZhenHua; LV ChaoQun (Jixie qiangdu)
In order to solve the problem of safety assessment effectively for subsea oil and gas pipeline,the rules about pipeline residual strength changing with the defect geometric information such as length,width and depth were analyzed using finite element method（ FEM）,and on this basis the parameterized model of pipeline residual strength was obtained,and the unknown coefficients in the model were identified using improved genetic algorithm,thus the model can describe the quantitative relation between the residual strength and defect geometrical quantity. The experimental results show that the model is more reliable than the existing pipeline assessment criteria,it can be effectively used in residual strength analysis for subsea pipeline,the analysis results can provide theoretical basis for pipeline safety assessment.